Entrepreneurship and the concept of fit: A model and empirical tests - Naman, John L; Slevin, Dennis P. (Strategic Management Journal, 1993)
Abstract This paper reports the results of a study designed to investigate entrepreneurship and ‘fit’ in small and medium sized high technology manufacturing firms. A normative model of fit has been developed, which including the variables of entrepreneurial style, organizational structure, and mission strategy, determines a measure of the firm's fit with its environment. The normative model of fit proposed here is based on variables and relationships found to be important in previous empirical studies. Data on environmental turbulence, entrepreneurial style, organization structure, mission strategy, and financial performance were collected from 82 manufacturing firms. A measure of fit was calculated for each firm. Findings indicate that performance among firms was positively related to the measurement of fit. In short, fit is an important construct for firm success. Implications include prescriptive guidance to assist practitioners in diagnosing and correcting ‘misfit’ for individual firms.